The Impact of Physical Activity on Endometriosis Symptoms: A Literature Review - Wilkowska, Krystyna; Kaczorowski, Wojciech; Michałowski, Maciej; Sudomir, Maria; Knysak, Karol; Maj, Alicja; Szczerba, Mateusz; Hejnosz, Aleksandra; Jastrzębski, Michał; Piątek, Maja (Quality in Sport, 2025)
Introduction: Endometriosis is a benign proliferative disease characterized by the presence of endometrial tissue outside the uterine cavity. Some studies suggest that physical activity may have a positive influence on the symptoms of this medical condition. Aim of the Study: The aim of this review is to assess whether physical activity has a beneficial effect on the symptoms of endometriosis and to identify potential knowledge gaps or limitations in the studies conducted so far. Material and Methods: This review is based on studies identified through databases such as PubMed and Google Scholar, using the following search terms: “endometriosis and physical activity”, “endometriosis and exercise” and “treatment of endometriosis”. Results: Three of the analyzed studies provided evidence supporting the hypothesis that physical activity has a positive impact on endometriosis symptom management, particularly in reducing pain. Two other systematic reviews did not reach clear conclusions, and one study did not find statistically significant evidence of a beneficial effect of exercise on endometriosis management. Conclusions: The current literature does not provide consistent results regarding the impact of physical activity on endometriosis. Therefore, future studies, especially high-quality randomized controlled trials, are required to draw reliable conclusions.